Institutionalizing education and the culture of learning in medieval Islam: the Ayyūbids (569/966 AH) (1174/1263 AD) learning practices in Egypt as a case study - Merah, Souad; Tahraoui, Ramdane (IIUM Press, 2017)
Because of the political weakening of the central Abbasid caliphate in Baghdad, and the fragmentation of its vast dominions into sultanates and emirates, it was customary for those emerging Muslim sultanates in medieval Islam, both Sunni and Shii’, to manage and patronize the intellectual activities, including institutions of learning, curriculum, human capitals (scholars, and students) in a flexible manner. The intellectual life was not run by one particular office, though the educational policies in each of those sultanates were largely politicized like in the case of the Seljūks, Fatimids and the Ayyūbids. Some researchers in the history of Islamic education attributed the involvement of the state into different educational activities to another political and cultural factor that is the emergence of dogmatic, philosophical and legal debates and subsequently sectarianism. These factors have had a negative effect on the independent culture of learning which dominated the liberal character of Islamic education for many decades. This paper highlights the process of institutionalizing education and its effect on the culture of learning during the rule of the Ayyūbid sultanate. It aims to unveil the effect of the measures taken by the Ayyūbids in formalizing education and show the visible dominance of military and political elites on the intellectual life, an influence which heralded the death of the customary Muslim conventional and liberal style of learning. The results of this research show that despite the success of the Ayyūbids in their endeavor to restore Sunnism in Egypt, the autonomy that Sunni ‘ulama maintained in early Islam up to the military Seljūks deteriorated further under the Ayyūbid military patronage. However, the official formal institutions of education never replaced persons as the focus of intellectual life. Informal and formal instruction was available for pupils in their own homes or in the privacy of learned scholars and wealthy individuals.